Clinical advances: pregnancy in gastroenterologic and hepatic conditions. Issue 5 (9th February 2023) - Kane, Sunanda V; Reau, Nancy
Abstract : The fields of gastroenterology and hepatology, along with endoscopic practice, have seen significant changes and innovations to practice in just the past few years. These practice changes are not limited to gastroenterology, but maternal fetal medicine and the care of the pregnant person have become increasingly more sophisticated as well. Gastroenterologists are frequently called on to provide consultative input and/or perform endoscopy during pregnancy. To be able to provide the best possible care to these patients, gastroenterologists need to be aware of (and familiar with) the various nuances and caveats related to the care of pregnant patients who either have underlying gastrointestinal (GI) conditions or present with GI and liver disorders. Here, we offer a clinical update with references more recent than 2018, along with a few words about SARS-CoV-2 infection and its relevance to pregnancy.